The necessity of an integral Christian worldview: reconnoitring the challenges for influencing the unbelieving world - Theron, P. M. (Koers, 2009)
Christians often conclude from the apostle Paul’s warning: “Do not be yoked together with unbelievers” (2 Cor. 6:14), that he condemns all contact with non-Christians and advocates total withdrawal from the world. However, Christians are called to “influence the world”. They need to find the fine balance between an exclusive and an accommodating Christianity. Being continously aware of and grounded in the Christian worldview will guide Christians to realise their calling to be “reformers” in all spheres of life. Christians are called to contribute to society’s transformation by means of a compre-hensive view of full-time service to God in every area of life. Christianity can only influence the world effectively if it is grounded in an integral Christian worldview and continually addresses the economy, politics, society, culture, religion, education and society as a whole. Flowing from the discussion, proposed guidelines for influencing the unbelieving world will be given at the end of the article.